Ideological representations of people with mental illness in Malaysian online newspapers: a critical discourse analysis - Niveethene Murugaiah; Marlina Jamal; Manjet Kaur Mehar Singh (Penerbit Universiti Kebangsaan Malaysia, 2024)
The news media’s role in shaping knowledge about mental illness has long been recognised as one of the primary conduits through which the public learns about people with mental health conditions. Despite a proliferation of research on media portrayals of mental illness, there seems to be a lack of studies critically examining how people with mental illness (PwMI) are constructed in mainstream and independent newspapers, especially in the Malaysian context. The present study aims to comparatively examine how PwMI are ideologically represented in mainstream and independent online newspapers. Predicated on van Dijk’s (1980) theory of semantic macrostructures and van Dijk’s (1998) ideological square model, twelve news reports from each newspaper were analysed. Findings revealed that the semantic macrostructures constructed from the news reports mainly centred on the topic of the dangerousness, vulnerability, and human rights of PwMI. The prominent “othering” of PwMI was particularly evident in both newspapers, as they were not only depicted as dangerous and violent but also as vulnerable, dependent, and powerless, in juxtaposition to those without mental illness. In addition to providing insights on how online newspapers contribute to the ideological construction of PwMI via topicalisation, the study’s findings have potential implications for media literacy programmes aiming to empower news consumers with critical reading skills in deconstructing public discourses on mental illness.